Effect of particle size on compositional, functional, pasting, and rheological properties of teff [Eragrostis teff (zucc.) Trotter] flour - Berhanu Regassa Jima; Agimassie Agazie Abera; Chala G. Kuyu (Applied Food Research)
Teff, a gluten-free cereal crop vital to Ethiopian cuisine, makes injera, a unique flatbread. However, the quality of teff-based products can vary depending on the teff flour particle size used, even if the same variety of teff is used. This study evaluated the effect of teff flour particle size on its nutritional profile, functional characteristics, pasting behavior, and rheological properties. Three particle size categories (fine, medium, and coarse) were compared to whole teff flour (control). The results showed that smaller particle sizes resulted in lighter colors, increased water and oil absorption, and lower bulk density. Pasting properties were influenced by particle size, with finer particles exhibiting higher peak viscosity. Fine particles also had a lower bulk density (0.68 g/mL) than coarse particles (0.77 g/mL). The rheological analysis revealed that teff flour, regardless of particle size, displayed solid-like behavior (elasticity (G') > viscosity (G'')). Moreover, the particle size significantly influenced proximate composition: moisture (8.79–9.05 %), protein (9.12–11.27 %), fat (2.54–3.00 %), ash (2.02–2.61 %), fiber (1.92–3.31 %), and carbohydrates (71.69–74.11 %). Coarser flour exhibited higher mineral and phytochemical concentrations due to the presence of an outer layer. Fine particles (0–180 µm) showed unique functional properties, making them particularly suitable for producing high-quality injera.